Luminescent properties of LaI₃-Ce microcrystals embedded in NaI host - Pushak, A.S.; Vistovskyy, V.V.; Demkiv, T.M.; Datsyuk, Yu.R.; Kravchuk, I.M.; Karplyuk, L.T.; Gektin, A.V.; Voloshinovskii, A.S. (Functional Materials, 2015)
Luminescence-kinetic properties of LaI₃-Ce microcrystals of 1-10 μm size in NaI-LaI₃-Ce system are studied upon 2.5-12 eV excitation using synchrotron radiation. The luminescent properties of cerium centers in the embedded LaI₃-Ce microcrystals are revealed to be similar to those for the bulk LaI₃-Ce crystals. The mechanisms of cerium centers luminescence excitation in the NaI-LaI₃-Ce crystalline system upon excitation in the transparency and fundamental absorption range of NaI and LaI₃ matrixes and mechanisms of thermal quenching of cerium ions luminescence in the LaI₃ microcrystals are discussed.